10 Anaemia: incomplete revascularisation and 12 months mortality after acs-pci compared to patients without anaemia!. (27th November 2017) - Yazji, Khaled; Abdul, Fairoz; Elangovan, Senthil; Haq, Muhammad Zia Ul; Ossei-Gerning, Nick; Anderson, Richard; Kinnaird, Tim
Abstract : Introduction: Anaemia is associated with adverse outcomes in patients presenting with an acute coronary syndrome. There is little published data on the effect of anaemia on the influence of completeness of revascularisation on 12 month mortality. Methods: Using standard WHO anaemia criteria, the influence of anaemia on patient demographics, PCI procedures and outcomes was studied. Data was sourced from hospital databases for patients admitted to a single centre between 2011 and 2014. Results: Of 1731 patients, 468 (26.9%) patients were anaemic. In anaemic patients, the mean CRUSADE score (34.6±16.9 vs 24.6±13.4, p<0.0001), mean GRACE scores (165.8±44.9 vs 141.6±40.1, p<0.0001) and percentage of patients with a high/very high CRUSADE score combined with a high GRACE score (69.3 vs 48.3%, p<0.0001) was much greater than patients without anaemia. Patients with baseline anaemia were more likely to have left main or chronic occlusive disease, and a greater number of diseased vessels and lesions. The percentage of patients with residual disease (41.2 vs 30.7%, p<0.0001), the number of residual diseased vessels (0.59±0.83 vs 0.42±0.72, p<0.0001), and a residual CTO (62.4 vs 56.4%, p=0.036) were all higher than in non-anaemic patients. In multivariate analysis, in patients with and without anaemia, age and number of residual vessels were the strongest predictors of 12 month mortality. Conclusions: Patients with anaemia present with complex coronary disease. Incomplete revascularisation closely correlated with increased mortality at 12 months irrespective of anaemia status.